Gender-based differences in the acceptance of rape myths in India: A comparative study - Bajaj Harshita (Temida)
Rape remains one of the most concerning crimes against women in India, with numbers continuing to rise every year. It is not just a crime against the victim but an offence against society. There are many myths about this crime which warrant a study. This study aims to understand whether there are differences in how males and females perceive rape myths. It is hypothesised that there might be a slight difference in the acceptance of rape myths between the two genders. This assumption is based on the fundamental understanding of gender roles and the societal status each gender holds. These stark and contrasting expectations of gender roles have contributed to typical behaviours and beliefs, which influence their acceptance of rape myths. The findings of the study reveal that, in most cases, males had a negative view of women and often accepted rape myths that blamed the woman. Additionally, it was found that males were more likely to agree with beliefs that did not hold men accountable for their acts of rape.